Conhecimento popular sobre o uso de plantas medicinais e o cuidado de enfermagem - Badke, Marcio Rossato (2008)
This work aims at knowing the conceptions and practices of the inhabitants at the community attended by the Bela União Family Health Unit, located at the city of Santa Maria/ RS, regarding the therapeutic use of medicinal plants on health care. The research has a qualitative approach and its data collecting instrument is composed by a semi-structured interview scheme and by observations. The individuals to be interviewed were selected according built relations network which involved ten individuals. The data examination was made by means of thematic analyses as proposed by Bardin (2008), that allowed to organize the data in such a way to make possible the appearance of thematic categories. While studying the emerging categories we can perceive that most of the popularized knowledge was acquired in the familiar environment, being the woman the one to retain and diffuse this knowledge. It was also observed the use of the home-made tea as a practice used in health maintenance and rehabilitation; it is a very common practice among the participants who besides using it in their day-life also mentioned the intention to cultivate herbs in their own homes. The individuals interviewed demonstrated the desire to acquire new knowledge about this subject despite the fact that most of the medicinal plants used by them have its popularized therapeutic indications similar to those found in the scientific literature. Therefore, we believe that this research has a great importance not only for nurses but also to society, because it points towards the need of an approximation between popular and scientific knowledge and, the production of projects that deal with this topic. Moreover, we suggest that nurses work in the integrality perspective, respecting people differences and social context. To do so, it is necessary to include, in nurse formation as well as in their permanent education, the knowledge of supplementary practices on health care with the use of medicinal pants.